OP0243 SERPINA3N LIMITS CARTILAGE DESTRUCTION IN OSTEOARTHRITIS BY INHIBITING MACROPHAGE-DERIVED LEUKOCYTE ELASTASE. (2nd June 2020) - Latourte, A.; Combier, A.; Jaulerry, S.; Cherifi, C.; Jouan, Y.; Ea, H. K.; Cohen Solal, M.; Hay, E.; Richette, P.
Abstract : Background: Interleukin-6 (IL-6) plays an important role in osteoarthritis (OA). Transcriptomic analyses (RNAseq) revealed that SerpinA3N, a serine protease inhibitor, is a key target of IL-6 in chondrocyte. Objectives: This study aimed to examine the role of SerpinA3N and Leukocyte Elastase (Elane), a serine protease targeted by SerpinA3N, in cartilage destruction during OA. Methods: The role of SerpinA3N was investigated in the destabilization of medial meniscus (DMM) model of murine OA with 1) mice with conditional inducible knockdown of Serpina3n in cartilage ( Col2 Cre ER ; Serpina3n fl/fl mice [ΔSerpina3n Col2 ]) and 2) C57BL/6 wild type (WT) mice treated with intra-articular injection of SerpinA3N (1, 5 or 15 nM/week). OA joint lesions were assessed by histology (OARSI and synovitis scores) and micro-CT analysis (osteophyte volume, subchondral bone remodeling). Because serine proteases targeted by SerpinA3N are not produced by murine chondrocytes, Elane expression (qRT-PCR) was determined in murine macrophages (Raw) stimulated or not by IL-6 (100 ng/ml). Recombinant SerpinA3N (30 nM) and a specific Elane inhibitor, Sivelestat (100 µg/ml) were used on cartilage explants treated by conditioned medium of macrophages pre-treated or not by IL-6 (CM–IL-6). Cartilage catabolism was determined by histology and matrix metalloproteinase MMP-3 production was evaluated by Western Blot and immunohistochemistry (IHC). Weekly intra-articular injections of Sivelestat (1mM) were performed in the DMM to determine the role of Elane in OA. Results: ΔSerpina3n Col2 mice had more severe OA lesions than control littermates 6 weeks after DMM, with greater cartilage damage (mean±SD OARSI score: 5.6±0.4 vs 3.4±0.5, p=0.01), increased synovitis scores (3.0±0.3 vs 1.9±0.3, p=0.03) and bigger osteophytes (7.2±0.8x107 vs 3.8±0.8x107 µ3, p=0.048). Conversely, WT mice treated with intra-articular injections of SerpinA3N 15nM exhibited less severe cartilage loss than mice treated with PBS after DMM (OARSI score: 2.1±0.4 vs 3.9±0.5, p=0.02). Elane mRNA expression was increased in macrophages upon IL-6 stimulation. In cartilage explants, CM–IL-6 activated cartilage catabolism and MMP-3 production, and effect that was blunted by SerpinA3N and Sivelestat. Finally, mice treated with intra-articular injections of Sivelestat had less severe cartilage damage than those treated with PBS after DMM (OARSI score: 3.3±0.47 vs 5.8±0.53, p=0.0046). Conclusion: SerpinA3N protects against experimental OA via the inhibition of Elane, a pro-catabolic serine protease produced by macrophages. This results highlight the crosstalk between cartilage and surrounding macrophages and open up new therapeutic perspectives. Acknowledgments: This work has been supported by French Society of Rheumatology and ART Viggo association. Disclosure of Interests: None declared